SEMANTIC MOTIVATIONAL AND CULTURAL CHARACTERISTICS OF LEXICAL UNITS DENOTING TIME IN ENGLISH AND UZBEK (Proceedings of International Educators Conference, 2023)
This article explores the semantic, motivational, and cultural characteristics of lexical units referring to time in the English and Uzbek languages. Employing a comparative linguistic approach, the study investigates how these languages conceptualize and express temporal concepts, shedding light on the cultural and motivational factors influencing time-related vocabulary. The research employs a combination of qualitative and quantitative methods, drawing insights from linguistic analyses and cultural studies. The findings contribute to our understanding of the diverse ways in which languages encode and reflect cultural perceptions of time.